The future past of tourism historical perspectives and future evolutions - McMahon-Beattie, Una; Yeoman, Ian (The future of tourism, 2020)
"This book offers a critical account of the historical evolution of tourism through the identification and discussion of key turning points. Based on these considerations, future turning points are identified and evaluated. The core findings of the book provide the first perspective on how the history of tourism will shape its future"--